Hybrid Energy Harvesting Scheme Using Piezoelectric and Thermoelectric for Wireless Sensor Nodes - Abdal-kadhim, Ali Mohammed; Leong, kok Swee (International Journal of Integrated Engineering, 2019)
This paper presents an evaluation of the effectiveness of a hybrid energy harvesting scheme for WSNs applications. Unlike common energy harvesting approaches that utilize a single microgenerator harvesting from a single source of energy, this hybrid scheme harvesting two energy sources which are ubiquitous from the ambient environment which are heat and vibration. The novelty of this work lies in the hybrid topology of an AC microgenerator and a DC microgenerator combined as a single energy harvester, where it will increase the chance of survivability of wireless sensor nodes. From the experimental result, it shows that the wireless sensor node powered via the hybrid energy harvester is able to survive in an environment where there are lack of mechanical vibration or heat emissions. Moreover, the study on the time required to fully charge an energy storage element is also presented with a 15mf-16v capacitor by an electrical input of 5V with two different topologies of the harvesters which are arranged in parallel and serial.